Establishing reference intervals for von Willebrand factor multimers - Pikta, Marika; Vasse, Marc; Smock, Kristi J.; Moser, Karen; van Dievoet, Marie-Astrid; Lejniece, Sandra; Szanto, Timea; Bautista, Hector; Nouadje, George; Banys, Valdas (Journal of Medical Biochemistry, 2021)
Background: von Willebrand factor (VWF) multimers (VWF:MM) methodologies are technically difficult, laborious, time consuming, non-standardized and results vary between laboratories. A new semi‐automated VWF:MM assay is available for routine use (Sebia). Due to lack of reference values for VWF:MM fractions, results interpretation can be challenging in some cases.Aims: The aim of this study was to determine reference intervals for low molecular weight (LMWM), intermediate molecular weight (IMWM) and high molecular weight (HMWM) multimers.Methods: Samples of 134 healthy individuals were analyzed. Acceptance criteria: no history of hemorrhagic episodes; no usage of any interfering medication for at least 10 days before blood collection; normal coagulation screening tests; normal VWF screening assay results; written consent provided.Results: After outlier exclusion (n=3), done by Grubs double sided and Tukey methods, a total of 131 samples were analyzed statistically. The proposed reference intervals for VWF:MM were calculated for LMWM 10.4-22.5%, IMWM 22.6-37.6%, HMWM 45.6-66.6%.Conclusions: Quantification of VWF:MM fractions, in addition to qualitative assessment of VWF:MM patterns, has the potential to aid in differential diagnosis of von Willebrand disease (VWD) subtypes. The reference values calculated in this study can be used in future research to establish clinical decision limits.
Keywords: von Willebrand factor, von Willebrand factor multimers, quantitative analysis, reference intervals